Lithuanian Consumers Expectations and Their Assessment - Misiūnas, Algimantas; Jazukevičiūtė, Rūta (Lithuanian Journal of Statistics, 2012)
In the first part of the paper the historical development of consumer expectations, the evolution and estimation of themain expectations theories, the impact of economical expectations various economic processes are reviewed through the analysis ofliterature. The second part of the paper presents consumers surveys that provide a possibility to evaluate and track consumerexpectations.After the analysis of literature the author carried out a study to model alternative methods that could reflect consumer’sexpectations. The results of consumer surveys in Lithuania were the main information source for the research. In the researchprocess, the author analyzed the fluctuations and compositions of consumer confidence indicators.The conclusions and recommendations summarize the main concepts of the analysis literature and the main results of theresearch performed. The results of the study could be useful to economic policy-makers, business representatives, analysts and otherpersons concerned.
Keywords: consumer expectations; tendencies; confidence indicators; econometric analysis